PENGARUH BEBAN KERJA, PENGEMBANGAN KARIR DAN KOMPETENSI TERHADAP KINERJA PEGAWAI PADA PT. KERETA API INDONESIA DIVRE IV TANJUNG KARANG - Pita Septiana; Andi Surya; Yudhinanto Yudhinanto; Hasbullah Hasbullah; Desmon Desmon; Yulistina Yulistina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the impact of Workload (X1), Career Development (X2), and Competence (X3) on Employee Performance (Y) at PT. Kereta Api Persero Divre IV. A questionnaire was distributed to 175 respondents, and the collected data were analyzed using SPSS version 25. The t-test results show that Workload has a significant negative impact on Employee Performance (t-value = -6.065; significance = 0.000), with a regression coefficient of -0.228. Career Development has a significant positive impact on Employee Performance (t-value = 10.787; significance = 0.000), with a regression coefficient of 0.431. Competence also has a significant positive impact on Employee Performance (t-value = 9.717; significance = 0.000), with a regression coefficient of 0.396. The simultaneous test indicates that Workload, Career Development, and Competence together significantly affect Employee Performance (F-value = 216.353; significance = 0.000), with an Adjusted R-Square of 0.775.